Kathā sāgara, arathāta, Srī Japu Jī saṭīka : bhāwārathāṃ, pramāṇāṃ, sākhīāṃ ate sharadhā pūrana mahātama sahita - Sodhī, Tejā Siṅgha (SAMP early 20th-century Indian books project, 1954)
Critical study of Japujī, a work by Guru Nanak, 1469-1538; includes interpretative notes.